2011
DOI: 10.1021/ci200278w
|View full text |Cite
|
Sign up to set email alerts
|

String Kernels and High-Quality Data Set for Improved Prediction of Kinked Helices in α-Helical Membrane Proteins

Abstract: The reasons for distortions from optimal α-helical geometry are widely unknown, but their influences on structural changes of proteins are significant. Hence, their prediction is a crucial problem in structural bioinformatics. For the particular case of kink prediction, we generated a data set of 132 membrane proteins containing 1014 manually labeled helices and examined the environment of kinks. Our sequence analysis confirms the great relevance of proline and reveals disproportionately high occurrences of gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 31 publications
1
40
0
Order By: Relevance
“…In addition to Proline, studies have suggested other amino acids that could be important in kink occurrence, but none have been consistently identified. For example, Glycine has been found to be prevalent around kinks in some studies, but not in others . Similarly, Serine has been identified as a factor in kinks in some studies, but not in all .…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…In addition to Proline, studies have suggested other amino acids that could be important in kink occurrence, but none have been consistently identified. For example, Glycine has been found to be prevalent around kinks in some studies, but not in others . Similarly, Serine has been identified as a factor in kinks in some studies, but not in all .…”
Section: Introductionmentioning
confidence: 98%
“…While some methods have a binary classification of helices (kinked/straight), others have a ternary system (kinked/curved/straight or kinked/distorted/straight). The algorithms used to define the helix set also differ, these studies use methods such as DSSP, the PDB annotation, or manual inspection . As a consequence, the methods do not consistently identify the same set of helices as kinked.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meruelo et al [24] proposed a neural network approach, TMKink, and achieved a result with sensitivity and specificity of 0.7 and 0.89, respectively. Recently, Kneissl et al [25] suggested the use of string kernels for support vector machines to predict kink positions, which showed about 80 % of all helices can be correctly predicted as kinked or non-kinked. However these methods fail to provide reliable predictions of helical kink angles.…”
Section: Introductionmentioning
confidence: 99%